Biomechanics during cross-body lunging in individuals with and without painful cam and/or pincer morphology. (June 2020) - Graffos, Angelo; Mohtajeb, Maryam; Mony, Michelle; Esculier, Jean-Francois; Cibere, Jolanda; Wilson, David R.; Zhang, Charlie; Zakani, Sima; Hunt, Michael A.
Abstract: Background: Femoroacetabular impingement is a patho-mechanical hip condition that can lead to restrictions in hip motion, particularly in end-range hip flexion, adduction and/or internal rotation. Radiographic evidence of femoroacetabular impingement – cam and/or pincer morphology - is prevalent in the general and athletic populations. There is, however, a lack of studies that have analyzed the performance of sport-specific movements in people possessing these morphologies. Therefore, the purpose of this study was to compare cross-body lunge biomechanics between individuals with and without painful cam and/or pincer morphology. Methods: This was an exploratory, cross-sectional study where nine participants with cam and/or pincer morphology and symptoms, thirteen participants with asymptomatic cam and/or pincer morphology, and eleven pain-free controls performed the cross-body lunge during a single session. Trunk, pelvis, hip, knee and ankle kinematics, as well as hip, knee and ankle kinetics and vertical ground reaction forces were examined. Findings: Overall, the groups performed the movement similarly, with most variables statistically similar between groups. However, pelvis sagittal plane excursion throughout the entire cross-body lunge was significantly larger in those with cam and/or pincer morphology and symptoms compared to those with asymptomatic cam and/or pincer morphology ( P  = .046, effect size = 0.98). Interpretation: The results of this study show that cross-body lunge performance is similar across individuals with and without painful cam and/or pincer morphology. However, future research should aim to better understand pelvis biomechanics during sporting activities, as pelvis sagittal plane excursion may have important implications in rehabilitation and sport performance. Highlights: Cam and/or pincer morphology has a minimal effect on cross-body lunge performance. Presence of hip pain has a minimal effect on cross-body lunge performance. Pelvis sagittal plane excursion was the only statistically significant variable. Overall, findings are consistent with previous biomechanical studies in this area. Findings question the use of biomechanics to guide clinical management in this area.